Erectile dysfunction and exosome therapy - Feng, Huan; Peng, Wei; Deng, Zhiyao; Liu, Jihong; Wang, Tao (Frontiers in Endocrinology, 2023)
Erectile dysfunction (ED), as a common male disease, can seriously reduce the life quality of men and their partners. With the improvement of human living standards, ED is considered to be an important health issue that plagues men. However, it is difficult for existing therapeutic approaches to meet the needs of all patients, so it is necessary to develop novel treatment strategies. Exosomes, as a class of vesicles secreted by cells with bilayer membrane structure, are involved in various physiological and pathological processes in human body and considered to have great therapeutic potentials. This review summarizes the recent advances on exosome therapy with animal models of ED, and proposes the prospect of future research in order to provide a basis for clinical trials and clinical translation.